2015
DOI: 10.1093/ageing/afv024
|View full text |Cite
|
Sign up to set email alerts
|

Fear of falling is common in patients with type 2 diabetes and is associated with increased risk of falls

Abstract: type 2 diabetes is associated with increased fear of falling and fear-associated activity restriction, and this modifies the risk of falls even in the face of increased falls risk factors including worse mobility. Future studies of falls in diabetes need to consider that fear of falling is an important modifier of the relationship between risk factors and falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
58
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 29 publications
1
58
1
2
Order By: Relevance
“…The relationship between balance and FOF in older people has been reported in many studies. [13,23,24] But little has been published on the relationship between balance and FOF in older patients with DM. Valpato et al [5] found that diabetes is associated with an increased risk of falling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The relationship between balance and FOF in older people has been reported in many studies. [13,23,24] But little has been published on the relationship between balance and FOF in older patients with DM. Valpato et al [5] found that diabetes is associated with an increased risk of falling.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown that, age was an important factor for disturbed balance and FOF. [13,28] The patients in the current study were between 61-80 years. In this age range, we have found that balance and FOF were not affected by age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 It is a significant cause of morbidity, with symptoms ranging from pain and frequent falls to limb amputation secondary to inability to detect injury. 3,4 Many causes of peripheral neuropathy are treatable, and as such, conscientious effort must be made to identify the underlying etiology. 5 The older estimation of approximately 25% of peripheral neuropathy being idiopathic after a thorough evaluation 6 is likely reduced with modern testing.…”
mentioning
confidence: 99%